'I Would Rather Be Having My Leg Cut off Than a Little Needle': A Supplementary Qualitative Analysis of Dentally Anxious Children's Experiences of Needle Fear - Fiona Noble; Jennifer Kettle; Joe Hulin; Annie Morgan; Helen Rodd; Zoe Marshman (MDPI AG, 2020)
Fear of needles is common in childhood, with up to 50% being affected to some degree. In individuals who are dentally anxious, the prevalence may be as high as 91%. Fear of needles, and therefore intra-oral injections can have negative impacts on children's quality of life and healthcare experiences, including a requirement for pharmacological methods to facilitate dental treatment. The aim of this study is to identify whether dentally anxious children report fear of injections and explore how these children experience a fear of needles in a dental setting. A supplementary analysis of interviews collected as part of two previous studies relating to children with dental anxiety. Five main themes were identified: feelings about needles; the nature of needle fear; the context of the fear, its consequences and how children tried to control the process. Children showed a desire to have control of their healthcare interventions, and wanted to trust the healthcare professionals giving the injections. There is evidence that children with dental anxiety also experience fear of needles, including intra-oral injections. Further primary qualitative research is needed to explore this topic in more depth and to design appropriate child centred interventions to reduce needle fear.